A autonomia da compensação e punição da indenização por dano extrapatrimonial, como instrumentos de efetivação do direito fundamental à proteção do consumidor - Pereira, Carlos Paulinelli (2023)
This dissertation analyzes the fundamental right from the constitutional perspective that advocates consumer protection as a fundamental right. In which the punitive function of compensation for extra-patrimonial damage autonomous from the compensatory function in the context of the contemporary legal system ensures greater guarantees for the defense of this right. Having as its scope the bibliographical review of current legal texts and texts of specialized doctrines, in constitutional law, civil and consumer law, as well as the reflections of the jurisprudence of the higher courts. Analyzing moral damage and its aspects, the possibility of applying the theory of punitive damages in Brazilian law, analyzing hypotheses of which situations an increase in compensation is accepted in order to achieve the pedagogical purpose, which has as its backdrop the objective of social pacification by the Brazilian legal system, as it inhibits harmful actions.